Building Bridges Supporting Families across Service Systems - Family Resource Coalition, Chicago, IL.; Goetz, Kathy; Family Resource Coalition, Chicago, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This double issue of the journal "Report" focuses on the collaboration among seven social service systems that support and serve children and families. Each of the sections discusses one of the seven systems, presents an overview essay, and profiles programs that execute the service. The first section, on education, emphasizes linkages between schools, communities, and families to ensure educational success. Section 2 is concerned with the child welfare system and its support for foster families providing physical and emotional safety for children. The focus of Section 3 is the health care system and its scope beyond traditional clinical care. Youth development is discussed in Section 4, as a parallel movement to family support. The program profiles deal specifically with low-income and minority families in African-American neighborhoods. Section 5 focuses on supporting people with disabilities through centers and home visiting programs. Section 6 is concerned with the welfare system and using a new approach of combining employment services with family services. The last section focuses on the child mental health system, which is concerned with services for children and adolescents with emotional and mental disturbances. (BAC)
Practitioners.
Family Resource Coalition Report, v13 n1-2 Spr/Sum 1994.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Blacks; Child Welfare; Community Involvement; Disabilities; Family Involvement; Family Programs; Foster Care; Health Services; Home Programs; Mental Health; Program Descriptions; Social Services; Welfare Services; Youth Programs; Family Support; Accelerated Schools -- African Americans -- Family Resource and Support Programs -- Family Resource Coalition IL -- Goals 2000 -- Networking -- School Based Health Clinics -- Schools Reaching Out Project -- Yale Child Study Center CT; Collected Works, Serials; Reports, Descriptive